Optimasi Keuntungan Bisnis Toko Kue Menggunakan Program Linear Metode Simpleks (Studi Kasus: Toko Kue Bread Islamy Bakery and Cake Shop) - Haloho, Agatha Christiorenfa Br; Siregar, Amanda Sartika Br; Zebua, Grace Selvi Monica; Azura, Sandra; Siregar, Siti Kholidjah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
A bakery business, or bakery in Indonesian, is a shop that produces and sells flour-based foods baked in the oven such as bread, pastry, cakes, donuts, pastries, cookies, pies, and many more. It is a problem if one of these ingredients is not fulfilled, production in the bakery business will be hampered. Therefore, to find out what variables hinder the optimum value in the bakery business, mathematical modeling can be made using the linear program of the simplex method. The method used is a qualitative descriptive method. Data collection techniques in this study include the use of primary data obtained through observation, interviews, or distribution of questionnaires to relevant sources. And secondary data are obtained through literature search from books and magazines relevant to the research topic. The analysis technique used is linear programming using the simplex method. The results and discussion of research show that the function has reached optimal conditions. Therefore, the calculation is stopped after all values in the goal function become positive. The result of the settlement shows that the maximum profit (Zmaks) is Rp. 69,626.